Exploring the Biomedical Frontiers of Plant-Derived Nanoparticles : Synthesis and Biological Reactions - Barathi, Selvaraj; Ramalingam, Srinivasan; Krishnasamy, Gopinath; Lee, Jintae (MPDI, 2025)
As contemporary technology advances, scientists are striving to identify new approaches to managing several diseases. Compared to the more popular physiochemical synthesis, the plant-derived combination of metallic nanoparticles using plant secondary metabolites as a precursor has a number of benefits, including low expenses, low energy consumption, biocompatibility, and medicinal usefulness. This study intends to explore the impacts of using plant-derived synthetic materials including metallic nanoparticles (NPs), emphasizing the benefits of their broad use in next-generation treatments for cancer, diabetes, Alzheimer's, and vector diseases. This comprehensive analysis investigates the potential of plant-derived remedies for diseases and looks at cutting-edge nanoformulation techniques aimed at addressing the function of the nanoparticles that accompany these organic substances. The purpose of the current review is to determine how plant extracts contribute to the synthesis of Silver nanoparticles (AgNPs), Gold nanoparticles (GtNPs), and platinum nanoparticles (PtNPs). It provides an overview of the many phytocompounds and their functions in biomedicine, including antibacterial, antioxidant, anticancer, and anti-inflammatory properties. Furthermore, this study placed a special focus on a range of applications, including drug delivery systems, diagnostics and therapy, the present benefits of nanoparticles (NPs), their biomedical uses in medical technology, and their toxicities.